KARAKTERISASI MUTU BIJI KAKAO (Theobroma cacao L.) HASIL FERMENTASI PADA BERBAGAI KONSENTRASI RAGI DAN WAKTU PENGADUKAN - Tulnafsi, Latifah; Alimuddin, Suraedah; Sabahannur, St. (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
This study aims to: (1) Assess the effect of tape yeast concentration on cocoa bean quality; (2) Assess the effect of stirring time on cocoa bean quality; (3) Assess the interaction between yeast concentration and stirring time on cocoa bean quality. This study was conducted at the Pangkep State Agricultural Polytechnic campus, Pangkep Regency, South Sulawesi Province. This study was conducted from June to August 2025. This study was arranged using a randomized block design with a two-factor factorial pattern. The first factor was the tape yeast concentration, consisting of 4 levels (0%, 1%, 2%, 3%), and the second factor was the stirring time, consisting of 2 levels (36 hours and 48 hours). The results showed that a 3% yeast concentration gave significant results on almost all cocoa bean quality parameters. The parameters included fat content (47.26%), moisture content (6.32%), acid content (1.75%), slaty beans (1.40), fermentation index (1.21), and bean pH (5.46). A 36-hour stirring time significantly affected several cocoa bean quality parameters, including fat content (46.25%), slaty beans (2.02), and bean pH (5.32). The interaction between a 3% yeast concentration and a 36-hour stirring time significantly affected the fermentation index, which was 1.21, and tended to produce a better number of beans, namely 84 beans per 100 grams, with grade AA.